How does emoji feedback affect the learning effectiveness of EFL learners? Neuroscientific insights for CALL research - Chen, Yen-Jung; Hsu, Liwei; Lu, Shao-wei (Computer assisted language learning, 2024)
It is well known that teachers' feedback plays an important role in students' learning, as it enhances learners' cognitive development; yet there has been little research on how positive feedback given in the form of emojis works in computer-assisted language learning (CALL) courses. In this study, an experiment was designed to clarify how English as a Foreign Language (EFL) learners' emotions are affected when such feedback is presented (no feedback vs. supraliminal feedback vs. subliminal feedback) and to examine how the feedback correlates with their learning effectiveness. A within-subject experiment with 33 participants was designed and administered to examine three proposed research hypotheses. Participants' frontal asymmetry alpha (FAA) and their recollection of the learning contents were used as the index of their emotional valence and learning effectiveness. The results revealed that positive feedback given in the form of emojis generated a positive/approach emotion when it was shown subliminally. Furthermore, a significant relationship was seen between EFL learners' positive emotion and their learning effectiveness; such a finding was supported by the significant relationship between the modes of emoji presentation and the participants' learning effectiveness. This study's originality and value lies in the innovative research method that was adopted and the interesting findings that it yielded. The limitations of this study such as research design and sampling are reported. The study also has practical and theoretical implications for practitioners and scholars of CALL for praxis and future research.